Ontology based framework for Tactile Internet and Digital Twin Applications - Adhami, Hikmat (Université d'Ottawa / University of Ottawa, 2022)
In the era of Industry 4 and Digital Twin – DT- (integrating Audio-Video, Virtual Reality, Augmented Reality and Haptics - from the Greek word Haptikos meaning "able to touch") and the Tactile Internet (TI), it becomes obvious that telecom stakeholders need different networks requirements to provision high quality services with respect to the new standards. In reality, this era is proposed as TI, and it will achieve a true paradigm shift from content delivery to skill-set delivery network types, thanks to recent technical breakthroughs. It will build a new internet structure with improved capabilities; but it will be difficult to meet the technical needs of the TI with current fourth generation (4G) mobile communication systems. As a result, 5G mobile communication systems will be used at the wireless edge and as a key enabler for TI due to its automated core network functionalities. Because of the COVID-19 outbreak, most daily activities such as employment, research, and education are now conducted online rather than in person. As a result, internet traffic has risen dramatically. Nowadays, Tactile Internet is in its infancy deployment phase worldwide. For this reason, and because of the growing need of its applications, the feasibility of these applications on the existing and deployed networks infrastructures, especially in the growing countries, is thought to be very hard, even quasi-impossible. Since 5G is not reaching yet its convergence stage (i.e. it is not deployed everywhere) and there is a huge stress on mobile communications given that the world is still facing the COVID-19 Pandemic, and since all the activities are taking place online, we propose design and implement a QoS framework to facilitate the feasibility and the applicability of the TI systems, where no 5G infrastructure is deployed. This framework will predict the most suitable network type to be deployed for certain given TI applications with certain given KPIs (Key Performance Indicators). Also, this framework is scalable, in such it gives an idea of even the future Next Generation Mobile Networks types (NGMN, if necessary). “To deal” with TI applications, means “to deal” with Haptics added to Audio and Video streams. Therefore, performance evaluation for haptic networks is required. And since there are different types of haptic networks, so interoperability is needed. Consequently, a standardization form is necessary for that purpose, to annotate and describe the haptic network. The first idea that flashes in mind, is the use of Ontologies. In these latters, we can add intelligent rules to infer additional data and predict resource requirements in order to achieve better performance. Many works in the research rely on Artificial Intelligence approaches to tackle the above-mentioned standardization, but very few depend on ontologies, and without futuristic outcomes, especially for the optimization problem. We mean by optimization, the optimal types, methods and rules that are able to accommodate the applicability of the TI systems (here come the applications KPIs) in an acceptable environment or infrastructure (here come the networking KPIs), and even-more, to infer the most optimal network type. To help manufacturing companies take full advantage of the TI, we propose to develop new methods and tools (ontologies) to intelligently handle the TI, DT (Digital Twin) and IoT (Internet of Things) sensor data and process data at the edge of the network and deliver faster insights. The outcomes of these ontologies, have been validated through two conducted case studies, where we simulated, in the first, TI traffic over Wi-Fi, WiMAX and UMTS (3G) infrastructures; While in the second we used 4G (LTE-A), along with SDN (Software Defined Networking) integrated to MEC (Mobile Edge Computing) as networking backbone. The results, in terms of QoS KPIs performance evaluation, present high relevance to our proposed Ontology outcomes.
Keywords: Ontology; Tactile Internet; Digital Twin; 5G; LTE-A; WiMAX; WiFi; SDN; NFV; MEC